Strategi Digital Marketing Fitur Emas Byond BSI Sebagai Investasi - Hersa Farida Qoriani; Adinda Wahyu Faradila; Erinatul Romadona Novianti; Salwatul Muslimah (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has driven the transformation of banking services, including Islamic banking, which is required to provide application-based innovations. One of these innovations is the e-gold (e-mas) feature in the Byond by BSI application, which enables customers to invest in gold digitally in a practical and Sharia-compliant manner. This study aims to analyze the digital marketing strategy applied to the e-mas feature and to identify the factors influencing customer adoption of the service. This research employs a qualitative approach with a descriptive design. The subjects consisted of six informants selected through purposive sampling, including bank employees and customers using the e-mas feature. Data were collected through semi-structured interviews, observation, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings indicate that the digital marketing strategy is relatively effective, as reflected by a 70% adoption rate among customers. The main factors influencing usage include ease of access, investment flexibility, and trust in the Sharia-based system. Furthermore, digital distribution and product quality are more dominant than promotional activities in encouraging service adoption. This study concludes that the success of digital marketing strategies is more strongly influenced by user experience than by promotional intensity. Therefore, improving system quality and enhancing customers’ digital literacy are essential to support the sustainability of digital financial services.